2008
DOI: 10.1074/jbc.m708954200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Homologous Genes, chlA and chlA, That Are Differentially Involved in Isocyclic Ring Formation of Chlorophyll a in the Cyanobacterium Synechocystis sp. PCC 6803

Abstract: The isocyclic ring (E-ring) is a common structural feature of chlorophylls. The E-ring is formed by two structurally unrelated Mg-protoporphyrin IX monomethylester (MPE) cyclase systems, oxygen-dependent (AcsF), and oxygen-independent (BchE) systems, which involve incorporation of an oxygen atom from molecular oxygen and water into the C-13 1 position of MPE, respectively. Which system operates in cyanobacteria that can thrive in a variety of anaerobic environments remains an open question. The cyanobacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 39 publications
2
87
0
Order By: Relevance
“…and chlorophyll a biosynthesis under low-oxygen conditions (Minamizaki et al, 2008). In addition, we observed upregulation of chlG (slr0056), encoding chlorophyll a synthase and downregulation of chlN (slr0750) and por (slr0506) in both strains (Table 2).…”
Section: The Absence Of Hik31 Alters Transcriptional Response To Low mentioning
confidence: 59%
“…and chlorophyll a biosynthesis under low-oxygen conditions (Minamizaki et al, 2008). In addition, we observed upregulation of chlG (slr0056), encoding chlorophyll a synthase and downregulation of chlN (slr0750) and por (slr0506) in both strains (Table 2).…”
Section: The Absence Of Hik31 Alters Transcriptional Response To Low mentioning
confidence: 59%
“…In the case of Synechocystis Δycf54, it may be that the small amount of Chl a produced by this strain is due to the presence of three orthologs of bchE in the genome of this organism. It once was believed that proteins encoded by these genes did not contribute to Chl biosynthesis (13); however, the recent finding that cyanobacterial bchE orthologs from two strains of Cyanothece restore BChl a biosynthesis in a bchE mutant of Rba. capsulatus demonstrates the activity of O 2 -independent BchE orthologs from oxygenic phototrophs (29).…”
Section: Discussionmentioning
confidence: 99%
“…Before the present study, only AcsF had been identified as a bona fide cyclase subunit (8,13). Ycf54 and its ortholog LCAA were subsequently discovered to be required for the normal activity of cyanobacterial and plant enzymes, respectively (21, 22), but the absence of genes encoding Ycf54 from acsF-containing anoxygenic bacterial phototrophs suggested that it might not be a catalytic subunit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AcsF homologs have since been identified in many photosynthetic eukaryotes including C. reinhardtii (18), Arabidopsis thaliana (19), and barley (15). Two acsF-like genes, sll1214 and sll1874, have been identified in Synechocystis PCC 6803 (hereafter Synechocystis) (20); Sll1214 is essential for growth under aerobic conditions (20) and, to a certain extent, micro-oxic conditions (21), whereas Sll1874 was found to be essential for growth in micro-oxic conditions (20,21).…”
mentioning
confidence: 99%